Vloga nevladnih organizacij pri uveljavljanju politik človekove varnosti - Železnik, Ana (Teorija in praksa, 2016)
Since human trafficking represents a threat to national, international and human security, it is discussed in the light of critical security studies. We place the concept of human security within the public policy process while highlighting the aspect of key policy actors. Based on analysis of the policy of assistance for the victims of human trafficking in the Republic of Slovenia as defined in the government programme and with the help of an ex-post evaluation of the effects of implementing the Aliens Act, our goal is to determine how the primary policy actors put human security onto the security agenda. Our findings reveal that NGOs are the key actors in shaping human security.
Keywords: človekova varnost; javna politika; nevladne organizacije; security; trgovina z ljudmi; varnost; varnostna politika; žrtve